PESAN DAKWAH DALAM FILM CINTA ANAK SHOLEH - Suci Rahayu; Penmardianto Penmardianto (KOLONI, 2022)
This study aims to find out what da'wah messages are and how the techniques for delivering da'wah messages are contained in the film Cinta Anak Sholeh episodes 1-5. The film Cinta Anak Sholeh is an Indonesian film produced by MNC Pictures which premiered on January 12, 2022. This film tells about two twin boys named Ali and Reyhan and the life that surrounds them. This film is relatively new in the world of research, so there are no researchers who have examined this film. This study used a qualitative method, namely the data collected in the form of words, documents, and pictures, using a descriptive qualitative approach. While the data collection used is documentation, where research data collection techniques are based on searching data in the form of DVDs, films, books (text books), theses, journals, internet sites, and so on which are considered relevant in this study. The result of this research is that the researcher found that the message of da'wah in the film Cinta Anak Sholeh is found in three fields, including the fields of faith, sharia, and morals. And the technique of delivering da'wah messages is taken based on the scene, sound effect, location and shooting technique. Keywords: Dakwah Messages, Techniques for Delivering Messages, Movies Love Sholeh Children